Modelling a Static VAr Compensator consist of TCR and TSC - Turan, Onur; Sarı, Yavuz (Fırat University, 2021)
As an alternative to traditional solutions, systems that flexible alternating current transmission systems (FACTS) have been developed in order to make electrical energy systems more efficient, to improve stability and power quality, and these systems have been used in different parts of the world including our country. In general, FACTS can be described as systems providing voltage, impedance and phase angle control in AC systems. With the recent studies, the use of modern technology devices such as static VAr compensator and static synchronous compensator is becoming more common in order to ensure the energy quality in power systems. Furthermore, due to the developments in semiconductor technology, static VAr compensation systems have been started to be applied on medium and high voltage side. The most important feature of these systems is that they can compensate without needing reactive power from the grid. In this study, necessary reactive power required by the system provided by using a static VAr compensator consisting of thyristor-controlled reactor and thyristor switched capacitor structures. In the simulation studies, the reactive energy is supplied through the static compensator instead of the voltage source. In this way, unnecessary capacity utilization in the system was prevented. It is recommended to use static VAr compensators especially where there is unbalanced load and instant reactive power is required.
Keywords: Engineering; Mühendislik